Locational Differences Of Gaseous Emission Effects From A Semi-Aerobic Landfill - Izhar, Tengku Nuraiti Tengku (2010)

(untitled)
Landfill gas is a mixture of methane (CH4), carbon dioxide (CO2) and small quantities of other odorous gas including ammonia (NH3) and hydrogen sulphide (H2S). The major problem associated with landfill sites in Malaysia are odour from waste decomposition, flies, vermin and leachate into nearby water body from the landfill. Recognizing the importance of landfill gas, the study investigated the effect of landfill gas on human being. Four landfill gas constituents (CH4, CO2, CO and H2S) were monitored from 15 December 2009 until 11 January 2010, a period of 28 days.